LEARNING STYLE AND STUDENTS' ACADEMIC PERFORMANCE, IS THERE ANY RELATION? - Syilvia Wenny J; Rian Dani (PRIMACY Journal of English Education and Literacy, 2023)
When a pandemic hit the entire planet almost one year ago, every facet of the teaching and learning process changed. It is included in the learning styles of students. Some problems were observed during online learning, particularly for students at the University of Muhammadiyah Jambi. Some students seemed to not have a good preparation in studying. There were some distractions when the learning process occurred online at that time. For their task, they were late in submitting the task. Because of these concerns, it appeared that there was some dispute about how students truly learnt through online learning. The purpose of this study was to report statistics on the different types of learning styles utilized by students in their English online learning. Neil Fleming's The VARK Questionnaire was used to analyze the data. The qualitative descriptive method was applied in this study. This study's population consisted of first semester Management Department students in the academic year 2020. There were three different classes: R.B1, R.A7, and R.B3. The findings revealed that most students in this study used a kinesthetic learning style. Then came auditory learning, which was followed by reading and writing learning styles. The final was visual learning style. Nevertheless, there was not a significant correlation between academic performance and students’ styles of learning based on the test results.